Development of a nutritional documentation tool: a Delphi study. Issue 6 (25th January 2019) - Berger, Stefanie; Eglseer, Doris; Eisenberger, Anna; Wirnsberger, Gerhard H.; Roller-Wirnsberger, Regina E.
Abstract: In daily clinical practice, the smooth, timely and comprehensive transfer of information between care settings is important and reflects a cornerstone of high-quality patient care. The integration of nutritional information in the medical information transfer is currently not included in an evidence-based approach. It was, therefore, the aim of this study to develop a nutritional documentation tool (NDoc) on the basis of evidence and test it for its usability in daily clinical practice. Based on the results of a literature review, the authors collected core content using a modified Delphi survey from experts across Europe and included the information collected in a structured, NDoc. The subsequently developed tool included thirty items and was tested for its usability on a daily basis among primary care physicians and clinical physicians. The new NDoc can be introduced for use in any computer-based hospital information system regionally and adapted for worldwide use.